Pengaruh Media Papan Hitung FPB dan KPK Terhadap Peningkatan Minat Belajar Matematika Siswa di MI Al-Azhar Ajung Jember - Crismono, Prima Cristi; Triana, Vivi; Pitasari, Mely Agustin Reni (Auladuna: Jurnal Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to examine the effect of using the FPB and KPK Calculation Board Media on students' interest in learning mathematics at MI Al Azhar Ajung. This media is designed to help students understand abstract mathematical concepts such as the Greatest Common Factor (GCF) and the Least Common Multiple (LCM) through a more visual and interactive approach. This study used a quasi-experimental design with a pre-test and post-test control group. The research sample consisted of 44 students divided into two groups: the experimental group using the FPB and KPK Calculation Board Media, and the control group using conventional learning methods. The results of the analysis showed that the experimental group experienced a significant increase in learning interest, with an average post-test score of 82.40, while the control group only reached 68.30. The Mann-Whitney test showed a p value = 0.002 (p <0.05), which indicated that the difference between the two groups was very significant. These findings indicate that the use of the FPB and KPK Calculation Board Media has a significant positive effect on increasing students' interest in learning mathematics. Therefore, the use of this learning media can be recommended as an effective alternative to improve students' motivation and understanding of mathematical concepts at the elementary education level.